If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10x+4=-6x-12
We move all terms to the left:
10x+4-(-6x-12)=0
We get rid of parentheses
10x+6x+12+4=0
We add all the numbers together, and all the variables
16x+16=0
We move all terms containing x to the left, all other terms to the right
16x=-16
x=-16/16
x=-1
| 24=4(x-7)÷8(1-6x) | | 3^x=49 | | 2x-3x+10=15 | | X2+y2=19 | | -5x-18=-28 | | e^2-2e-8=0 | | d²+7d-5=0 | | -45=6w+15 | | n-2=6n= | | 3/4b=12/2 | | 7k=8k-k | | 2x+14=3(x+5) | | 29.4+y=78.4 | | 8y-20=y+15 | | -5.2=5.1y-4.6y+5.3 | | 14.7+y=44.1 | | 4.9+y=19.6 | | 2(-5-1.5x)=-5(0.2-8) | | 3b/4=12/2 | | 2(-5-1.5x)=-5 | | 2t2+50=0 | | x×2/3+5=27 | | -6(v+3)+3v+5=5v+7 | | 5(x-3=5x-15 | | 42+1.3x=122-1.2 | | 40=7x-54 | | 2(6)-2x=3 | | -8=15x+22 | | 7(8-(-7x-5))=294x+266 | | (x-4)^2-9=16 | | 10x-26=9x-2 | | 9x+7-4(x+1)=8x+5 |